Adenoid cystic carcinoma of the lung: Response to tamoxifen after chemoradiation. Issue 2 (27th March 2014) - Liu, Jia; Hau, Eric; Links, Matthew; Graham, Peter H
Abstract: Primary adenoid cystic carcinoma of the lung is a rare subtype of lung cancer with a prolonged natural history but is difficult to completely resect surgically due to its proximal location. Hence radiotherapy plays a role for local control of these cancers. The role of systemic therapies in the treatment of adenoid cystic carcinoma of the lung remains unclear. Isolated case reports have previously described the treatment of primary adenoid cystic carcinoma of the lung with tamoxifen, resulting in partial control. We report the first case of primary adenoid cystic carcinoma of the lung treated with primary chemoradiotherapy due to unresectable location of the tumor, and disease stabilization with symptomatic response to tamoxifen following tumor recurrence. There is a need for further studies to investigate the role of anti‐hormonal therapies in the treatment of adenoid cystic carcinoma of the lung.